Health disparities among Deaf communities from Colombia: assessing communication, technology and healthcare access - Nora Groce; Jyoti Dalal; Minerva Rivas Velarde; Laura Catalina Izquierdo Martínez; Angela Martínez-R; Jess Cuculick (BMJ Global Health)
Introduction Despite efforts to improve health equity, there is still limited knowledge about the number and characteristics of people with disabilities, particularly the Deaf community. Our aim is to use linguistically and culturally adapted research instruments to measure key health indicators and priorities within the Deaf community from a low- and middle-income country—Colombia, contributing to a better understanding of health inequities.Methods We used data from the Health Survey for Deaf (HSD) and National Quality of Life Survey (NQLS) from Colombia. We included various communication and technology-related indicators—usage of smartphone, modes of interacting with healthcare personnel, along with health indicators—self-perception of health, healthcare quality, hospitalisation and functional difficulties in various domains. ORs were computed to depict the differences in two groups, adjusted for both age and gender, using logistic regressions.Results We included 204 and 877 Deaf participants from HSD and NQLS, respectively. Owning a phone was significantly associated with a better self-perception of health (ORs=2.27, 95% CI 1.63 to 3.17 for NQLS-Deafs; 1.49, 1.43 to 1.54 for NQLS-general population) but also with more functional difficulties corresponding to most domains (all ORs >1). However, for HSD datasets, we found that phone ownership was associated with having significantly less functional difficulties in moving hands (0.34, 0.14 to 0.81) and cognition (0.36, 0.15 to 0.89). Access to professional interpreting services was correlated with increased communication-related functional difficulties (2.02, 1.00 to 4.08), for HSD participants. Better self-perception of health was linked to fewer functional difficulties (all ORs <1), while recent hospitalisation was associated with more functional difficulties (all ORs >1).Conclusions We found that Deaf individuals generally experience poorer health outcomes compared with hearing individuals. To address these disparities, we recommend (1) improving data quality that could lead to targeted responses and monitoring of it and (2) implementing personalised health surveys that account for the Deaf population’s fluency in Spanish and Colombian Sign Language and their specific understanding of health issues.